Formation of aromatic ring structures during the thermal treatment of mallee wood cylinders at low temperature - Jiang, S.; Hu, X.; Xia, D.; Li, Chun-Zhu (Elsevier, 2016)
© 2016 Elsevier LtdAromatics are important components in the tars from biomass gasification or in bio-oil from pyrolysis. This study investigated the formation of polycyclic aromatics during the thermal treatment of mallee wood at low temperature. The formation of tar was negligible below 200 °C but became significant above 230 °C. At the same time, the abundance of aromatics also became significant above 230 °C. In addition, it was found that some aromatics were formed even at temperatures as low as 150 °C. These aromatics were trapped in the resultant chars but could be extracted with solvents (i.e. methanol/chloroform). The abundance of trapped aromatics was different between the outer surface and the centre of the char (cylinder shape). FT-IR and UV-fluorescence analysis revealed that the aromatics contained polar functionalities (e.g. carbonyl groups) on the benzene rings. Some unsaturated hydroxyl aldehyde/ketone intermediates were formed in parallel with the aromatics.